Mato Grosso: expressão aguda da questão agrária brasileira - Eduardo Paulon Girardi (Confins)
This work is the continuation of the article "A reading of the agrarian question in Mato Grosso" published in number 25 of the journal Confins in 2015 (GIRARDI, 2015). On that publication we defined the agrarian question, conducted a historical review of the agrarian question in the state of Mato Grosso and contextualized it on the whole of the Brazilian rural problems. Continuing the analisys of the theme in Mato Grosso state, from a regional approach, our goal in this article is to focus on some dimensions of agrarian Mato Grosso and analyze them throughout the Brazilian agrarian question and its interactions with the agricultural frontier.